Transient free convection flow of dissipative fluid past an infinite vertical porous plate - Soundalgekar, V.M.; Uplekar, A.G.; Jaiswal, B.S. (Archives of Mechanics, 2004)
A finite-difference analysis of transient free convection flow of a dissipative fluid past an infinite vertical porous plate is presented here. Velocity, temperature, skin-friction and Nusselt number are shown graphically and the effects of different parameters on the flow field are discussed.